Wheat Grain Yield Response to Seed Cleaning and Seed Treatment as Affected by Seeding Rate During the 2020–2021 Growing Season in Kansas - R. P. Lollato; L. O. Pradella; L. Ryan; L. M. Simão; N. Giordano; J. R. Soler; L. A. Haag (Kansas Agricultural Experiment Station Research Reports, 2022)
The objective of this project was to evaluate the winter wheat stand count and grain yield responses to seeding rate and its interaction with seed cleaning and seed treatment in Kansas during the 2020–2021 growing season. Experiments evaluating the response of the wheat variety SY Monument to three seeding rates (600,000, 900,000, and 1,200,000 seeds per acre), three seed cleaning intensities (none, air screen, and gravity table), and two seed treatments (none and insecticide + fungicide) were established in a split-split plot design conducted in a complete factorial experiment in ten Kansas locations. In-season measurements included stand count and grain yield. Despite a few location-specific results, the general trends were uniform to be generalized across locations as there were significant main effects of population and seed treatment for both stand and yield, but no significant seed cleaning effect or interactions among factors. Across locations, plant population increased with increases in seeding rate from 391,616 to 556,771 plants per acre from the lowest to the highest seeding rate, as expected. Seed treatment increased plant population from 467,778 to 492,211 plants/a. Grain yield increased from 68.8 to 72.5 bushels per acre as function of seeding rate, with higher yields associated with higher seeding rates. Grain yield increased from 69.8 bu/a in the untreated control to 71.8 bu/a when the seed was treated. This research is an initial step in evaluating the value of the seed certification process and does not compare certified seed versus bin-run seed. The seed used in this study was derived from a commercial seed production field (i.e., high quality seed) and not from commercial grain production fields.
Keywords: wheat; seed cleaning; seed treatment; seeding rate; seed size